Examining creative and design thinking as drivers of entrepreneurial orientation among university students in the startup sector - Benbedra, Amina (The International tax journal, 2025)
This study aims to explore the impact of creative thinking and design thinking on the entrepreneurial orientation of university students, with a particular focus on the mediating role of design thinking within the startup ecosystem. The research was conducted on a purposive sample of 66 first-year Master’s students majoring in Civil Engineering and Architecture at Ammar Telidji University of Laghouat. Data was collected through a structured questionnaire that addressed the dimensions of creative thinking (imagination, expression, and synthesis) and design thinking (inspiration, ideation, and implementation), in order to examine how these cognitive frameworks contribute to shaping students’ entrepreneurial orientation. The data was analyzed using SmartPLS, Jamovi, and Excel. The findings revealed statistically significant positive relationships between creative thinking and design thinking, as well as between design thinking and entrepreneurial orientation. While imagination and expression positively influenced design thinking, their direct effects on entrepreneurial orientation were negative—highlighting the necessity of design thinking as a structural bridge that translates unstructured creativity into effective entrepreneurial behavior. The synthesis dimension demonstrated limited and negative effects, suggesting challenges in integrating complex information...